Tata Cara Pemungutan Pajak dalam Perpektif Hukum Pajak - Suastika, I Nengah (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
This study aims to analyze the tax collection system, tax collection principles and tax collection system from a tax law perspective. This study is a normative juridical study to examine existing legal norms which are derived from statutory regulations. The data collection technique was carried out by means of literature study with the literature study guideline instrument that was developed independently. The data analysis technique is carried out descriptively, which begins with collecting data, reducing data, presenting data and drawing conclusions. The results of the analysis show that the tax collection system can be divided into three, namely the real system, the fictitious system and the mixed system. The principle of tax collection consists of the principle of domicile, the principle of source and the principle of nationality. The tax collection system consists of an official assessment system, a semi self-assessment system, a full self-assessment system and a withholding system. Based on the Indonesian tax law, the tax collection system uses the real system. Meanwhile, the principle of tax collection uses the principle of domicile, the principle of source and the principle of nationality. The tax collection system uses a self-assessment system where the taxpayer fills in according to statutory provisions.